Frankincense Revisited, Part I: Comparative Analysis of Volatiles in Commercially Relevant Boswellia Species - Niebler, Johannes; Büttner, Andrea (Chemistry & Biodiversity, 2016)
The genus Boswellia comprises a number of species which are famous for their production of frankincense, a fragrant gum resin. In the published literature, manifold studies on the volatiles and semivolatiles in individual samples of these gum resins exist, yet very few studies have investigated multiple samples. Contradictory results with regard to the volatile composition exist in literature. In this first part of the study, a large sample set (n=46) of mostly commercially obtained gum resins and essential oils was investigated by solid phase micro-extraction gas chromatography-mass spectrometry (SPME-GC-MS) or GC-MS. In the four commercially relevant species, namely B. sacra, B. serrata, B. papyrifera and B. frereana, 216 compounds were identified or tentatively identified, and the statistical evaluation of the resulting chemical profiles allowed a clear distinction between the species by their volatile profile. With only few exceptions, the designated species was found to be in accordance with the composition reported in reliable literature sources and detected in botanically identified samples. Chemotaxonomic marker substances were suggested to facilitate the differentiation of commercial gum resins or essential oils based on their volatile profil
Keywords: Boswellia; Burseraceae; Frankincense; Olibanum; SPME-GC-MS; Essential oil